Catharsis Through Cinema: An Italian Qualitative Study on Watching Tragedies to Mitigate the Fear of COVID-19 - Testoni, Ines; Rossi, Emil; Pompele, Sara; Malaguti, Ilaria; Orkibi, Hod (Frontiers in Psychiatry, 2021)
Background: Among different ways of coping with the unsettling situation of the COVID-19 pandemic, a very peculiar one has been identified: a more frequent request, by the general population, of movies or tv series related to the very theme of viruses, contagions, and epidemics. Objectives: The aim of the present study was to explore this peculiar phenomenon, in order to identify people’s emotions and cognitions during and after the process, and to better understand the possible psychological function cinema can have during moments of intense and generalized crisis like the present COVID-19 pandemic. Participants: Fifteen Italian adults took part in the study – eight women and seven men (average age = 30 years, SD = 10.54). Participants were recruited through social media via a specific announcement, and subsequently, through a “snowball sampling”. Method: For the present study a qualitative approach was adopted, and more specifically, the principles of Interpretative Phenomenological Analysis (IPA) have been followed. Semi-structured interviews were conducted by telephone or through online meeting platforms (Zoom or Skype). The written texts obtained from the transcription of each interview were analyzed using thematic analysis with the support of the software Atlas.ti, in order to highlight their fundamental contents. Results: From the data analysis, four main areas of thematic prevalence emerged, which reflected the participants’ condition during the pandemic that actually led them to watch epidemic-themed movies or tv series: the need to document themselves concerning the theme of epidemics, the need to exorcize contagion anxiety, the desire to find a character with which they could identify, and the casual condition of finding a peculiar movie related to the theme of pandemics and being interested in it because of the striking resemblance with real life. Conclusions: The findings suggest that cinema could indeed represent a powerful tool to help people face the intense uncertainty of the new COVID-19 epidemic, since it allows spectators to both obtain more insight into the current situation, and to project their fears and uncertainties into the movie or